CREDIT RESPONSE TO MONETARY POLICY SHOCKS IN NIGERIA: A COMPARATIVE ANALYSIS OF PUBLIC AND PRIVATE SECTORS USING VAR - Nze, Edwin (Economics and Statistics Research Journal (ESRJ), 2022)
This study investigates the response of credit to private and public sectors in Nigeria to shocks in monetary policy instruments using the vector autoregressive (VAR) model. Monthly data from 2010M1 to 2021M8 is employed to analyze the behavior of bank financial intermediation to monetary policy tools. Findings show that credit to private sector responds positively to shocks in money supply and monetary policy rate (MPR) in all periods, while the response to cash reserve requirement (CRR) was negative beginning from period five, and it also responded negatively to foreign interest rate shock. Credit to government responded positively to shocks in money supply up to period two and CRR in all the periods, but it responded negatively to MPR starting from period three. The study suggests that policies used to influence financial intermediation should take into account the sensitivity of both public and private sectors to these policy instruments and should factor in the impact of exogenous shocks